Optimizing of Electrical Submersible Pump with Stage Variation Using Nodal Analysis at “Rha” Well, Cepu Field for Enhancing Oil Production - Aditya, Rhera; Rohmana, Rian Cahya; Budiono (Penerbitan Universitas Trisakti, 2024)
Well “Rha”, located in Cepu Field, is an old well that no longer produces oil naturally (natural flow), so an artificial lift is needed to produce oil. The artificial lift method used in this well is an electrical submersible pump. The well has a maximum flow rate of 1016.04 BFPD with a water cut of 98.2%, indicating a significantly high proportion of water in the flow. The installed pump in this well is REDA DN450/42 Hz, with an operating range of 246–383 BFPD. The evaluation showed that the head pressure exceeded the maximum operating range, causing an upthrust. This research aims to optimize the installed pump by replacing it and performing nodal analysis to obtain the stage that matches the optimum flow rate. This study applied the Wiggins IPR method to calculate the well's maximum flow rate. The study identified and troubleshot performance issues with the existing pump and applied nodal analysis to optimize production. The optimal production rate in this well is 609.62 BFPD, which operates outside the DN450 pump's recommended operating range. Therefore, optimization was carried out using a new pump in the field DN750/42 Hz with 171 stages. Subsequent nodal analysis showed that 124 stages, with a horsepower of 10.01 HP and a pump efficiency of 56.42%, aligned with the optimal production rate. With a water cut of 98.2%, the initial oil rate was 5.2 barrels of oil per day (BOPD), which increased to 10.94 BOPD after optimization. This research demonstrates that optimization by adjusting the stages of ESP can achieve optimal production rates.